Platelet and ferritin as early predictive factors for the development of macrophage activation syndrome in children with Kawasaki disease: A retrospective case-control study - Zhang, Hua-yong; Xiao, Min; Zhou, Dan; Yan, Fan; Zhang, Yong (Frontiers in Pediatrics, 2023)
Objective: To investigate the early predictive factors for Kawasaki disease complicated with macrophage activation syndrome (KD-MAS). Methods: We performed a retrospective case-control study in children with KD from August 2017 to August 2022, involving 28 cases with KD-MAS and 112 cases not developing KD-MAS. Based on the univariate analysis, binary logistic regression was used to identify the early predictive factors for KD-MAS development, and the receiver operating characteristic curve (ROC) analysis was carried out to obtain the optimal cut-off value. Results: Two predictive factors were associated with the development of KD-MAS, which were PLT (OR = 1.013, 95%CI:1.001-1.026), and serum ferritin (OR = 0.991, 95%CI:0.982-0.999). The cut-off value of PLT was 110×10^9/L, and the cut-off value of serum ferritin was 548.4 ng/mL. Conclusion: Children with KD who had a PLT count under 110×10^9/L, and a serum ferritin level over 548.4 ng/mL are more likely to develop KD-MAS.